Critical thinking aspects manifested in secondary school students’ argumentative texts - Fatimah Fatimah (Universitas Pendidikan Indonesia, 2020)
To have a good skill at social participation and problem-solving, students need to embed critical thinking (CT) skills as early as possible. This study aims to explore critical thinking aspects manifested by secondary school students in writing one type of argumentative text, i.e. analytical exposition. Six eleventh-grade students and a teacher of a private school in one city of Indonesia participated in this study. Adapting Paul and Elder’s (2008), Ennis’s (1996), and Watson and Glaser’s (2009) frameworks, six students’ analytical exposition texts were analyzed to match CT elements, dispositions, and abilities. Moreover, six students and one teacher were also interviewed in responding to how adherent the CT disposition possessed by students. The findings indicated that only two texts manifested all aspects of CT, despite, still feebly. Those texts are categorized as dominant manifestation texts. Lack of providing reasons and evidence to strengthen arguments was the shortcoming of most writers. This research study contributes to students’ writing and thinking enhancement and to teachers in polishing the learning instruction.